Youth Services Forum: Past, Present, and Future - Shanna Hollich; Allyson Lauer; Amanda Liss (Virginia Libraries, 2013)
The Youth Services Forum (YSF) plays a prominent role in the Virginia Libraries Association (VLA), promoting quality library programs and services for children and youth across the Commonwealth. The Forum advocates for information access on behalf of Virginia’s young people; fosters the exchange of ideas and information among those who serve this age group; and presents awards to children’s book authors for outstanding writing in historical fiction, biography, and American history. YSF promotes reading as a year-round, life-long activity that is both enjoyable and essential for children of all ages.